2019
DOI: 10.2147/ott.s201373
|View full text |Cite
|
Sign up to set email alerts
|

<p>12-Lipoxygenase promotes epithelial–mesenchymal transition via the Wnt/β-catenin signaling pathway in gastric cancer cells</p>

Abstract: Background 12-Lipoxygenase (12-LOX) plays a major role in the progression and metastasis of various types of cancer. In gastric cancer (GC), the expression level of 12-LOX is significantly up-regulated; however, its function, and underlying mechanism of action remain unclear. Methods The mRNA and protein expression levels of 12-LOX were assessed using quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot analyses, respectively, in GC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A previous study reported that LOX cooperates with SNAIL at the protein level to facilitate the EMT and, thus, increases the invasive ability of breast cancer cell lines [46]. Another study also claimed that the overexpression of LOX promotes the proliferation, migration, and invasion of gastric cancer cell lines as well as high grade serous ovarian carcinoma [47,48]. In addition, PTX3 has pleiotropic roles in different types of cancer, such as gastric cancer, breast cancer, glioma, and prostate cancer.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study reported that LOX cooperates with SNAIL at the protein level to facilitate the EMT and, thus, increases the invasive ability of breast cancer cell lines [46]. Another study also claimed that the overexpression of LOX promotes the proliferation, migration, and invasion of gastric cancer cell lines as well as high grade serous ovarian carcinoma [47,48]. In addition, PTX3 has pleiotropic roles in different types of cancer, such as gastric cancer, breast cancer, glioma, and prostate cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, a research also explained that the stimulation of mTOR was induced by the activation of AKT [33]. In addition to this, excessive researches showed that the β-catenin signaling pathway controlled the development and metastasis of gastric cancer cells [34]. A report also explicated that some miRNAs participated in cell proliferation and migration via regulating AKT/mTOR and βcatenin pathways in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…The overexpression of ALOX12 gene, which codes for the arachidonate 12-lipoxygenase, is often a feature of cancer cells (Tomita et al, 2019). ALOX12 overexpression was shown to promote cancer metastasis (Zhong et al, 2018;Mi et al, 2020), epithelial-mesenchymal transition (Zhong et al, 2018;Yang et al, 2019), tumor growth, and cancer cell proliferation (Guo et al, 2011a). Conversely, the inhibition of 12-LOX decreases cancer cell proliferation and induces apoptosis of different cancer cell lines (Wong et al, 2001;Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%